Community Empowerment through Training and Coaching for Pulmonary Tuberculosis Prevention and Control: A Health Education Intervention Supporting SDG 3 - Efendi Sianturi; Elisabeth Surbakti; Maida Pardosi; Julietta Hutabarat; Meiyati Simatupang (Postgraduate, University of Mataram, 2026)
Tuberculosis (TB) remains a complex public health problem, not only because of the medical aspect but also because of the Stigma attached to it in society. Change agents such as cadres and recovered TB patients are crucial in disseminating information and reducing Stigma. Objective: This study aims to assess the effectiveness of training and Coaching in improving the knowledge and attitudes of cadres and recovered TB patients as agents of Change to prevent and control TB and reduce Stigma in the community. Method: The research design used a quasi-experiment with a pretest and post-test. Participants consisted of 20 people (16 recovered TB patients and four health cadres) from Tapian Dolok and Batu Anam villages. Data were analyzed using the Paired t-test. Results: There was a significant increase in the mean knowledge (from 48.00 to 95.50) and attitude (from 52.95 to 92.50) after the intervention, with a p-value of 0.001. All participants experienced an increase in the